Case Report: Atypical presentation of rickets with hypocalcemia-related emesis - Francioni, Andrea; Simone, Verena; Laschi, Elisa; Lonoce, Luisa; Mugnai, Francesca; Minerva, Michele; Cherubini, Davide; Grosso, Salvatore (Frontiers in Pediatrics, 2025)
BackgroundNutritional rickets, primarily resulting from vitamin D and/or calcium deficiency, is a well-recognized cause of skeletal and extraskeletal manifestations in children. However, gastrointestinal (GI) symptoms, such as vomiting, are not commonly reported as primary manifestations associated with hypocalcemia at the onset.Case presentationWe describe a case of a 9-month-old male infant of Afghan origin who presented to the Pediatric Emergency Department with a 7-day history of isolated postprandial vomiting. Physical examination revealed a large anterior fontanel, but no significant skeletal abnormalities. Laboratory blood evaluation demonstrated severe hypocalcemia, mild hypokalemia, and elevated alkaline phosphatase. Arterial blood gas analysis confirmed low ionized calcium and revealed metabolic alkalosis. Electrocardiogram showed a prolonged corrected QT interval (QTc). Intravenous administration of calcium gluconate and potassium led to rapid normalization of electrolytes and resolution of vomiting and QTc prolongation. Further investigation revealed severe vitamin D deficiency and elevated parathyroid hormone, consistent with nutritional rickets, which was confirmed by wrist radiographs. Oral supplementation with vitamin D3 and calcium carbonate resulted in complete resolution of symptoms and biochemical normalization at discharge and follow-up.ConclusionHypocalcemia can contribute to GI dysmotility and altered gastric secretion thus vomiting may be a possible symptom related to electrolyte disbalance of rickets. To date it is the first case report reporting isolated postprandial emesis as a presenting symptom of nutritional rickets. Clinicians should be aware of this unusual presentation to facilitate timely diagnosis and appropriate management, particularly in at-risk populations.